2023
DOI: 10.3390/bs13020083
|View full text |Cite
|
Sign up to set email alerts
|

Building Work Engagement in Organizations: A Longitudinal Study Combining Social Exchange and Social Identity Theories

Abstract: Starting from the insights of social identity theory and social exchange theory, the present study aimed to understand how social support and organizational identification relate to work engagement. Moreover, it sought to verify if social support and organizational identification interact with each other to explain work engagement three months later. A longitudinal study was conducted on a sample of 150 employees, in which organizational identification, social support, and work engagement were measured through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Indeed, social identity theory has also included affective components, such as the emotional significance and feelings of belonging that an individual gives to belonging, in its theorizations ( Nordhall et al, 2020 ) found that within a group of teachers, processes related to social identity, based on cognitive mechanisms (processes such as incorporation and assimilation into a new social group) and emotional mechanisms (attachment/belonging/closeness, pride, esteem), are essential for enhancing mental health and work motivation. The study by Simbula et al (2023) confirmed how, in line with theoretical conceptualizations of social identity and social exchange, factors such as identification and social relationships are significant in determining work-related well-being outcomes such as engagement. The study was carried out on workers in a longitudinal method; consequently, it appears that this position is also significant from a different angle in terms of time periods.…”
Section: Theoretical Foundations and Hypothesis Developmentsupporting
confidence: 56%
“…Indeed, social identity theory has also included affective components, such as the emotional significance and feelings of belonging that an individual gives to belonging, in its theorizations ( Nordhall et al, 2020 ) found that within a group of teachers, processes related to social identity, based on cognitive mechanisms (processes such as incorporation and assimilation into a new social group) and emotional mechanisms (attachment/belonging/closeness, pride, esteem), are essential for enhancing mental health and work motivation. The study by Simbula et al (2023) confirmed how, in line with theoretical conceptualizations of social identity and social exchange, factors such as identification and social relationships are significant in determining work-related well-being outcomes such as engagement. The study was carried out on workers in a longitudinal method; consequently, it appears that this position is also significant from a different angle in terms of time periods.…”
Section: Theoretical Foundations and Hypothesis Developmentsupporting
confidence: 56%
“…The study's revelations underscore the multifaceted nature of factors influencing employee turnover intentions within organizations (Cook & Rice, 2006;Simbula et al, 2023). The multi-dimensional aspects of employee value proposition, social identity, and employee engagement demonstrate the need for comprehensive strategies aimed at employee retention (Heger, 2007;Lazzari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to Simbula et al (2023), employees who perceive social support in the workplace and can rely on superiors for issue resolution are more likely to be engaged in their work, decreasing their intention to leave the organization. Additionally, Lazzari et al (2022) indicate that social identity indirectly affects turnover intention through employee engagement, emphasizing the mediating role of employee engagement.…”
Section: Employee Engagementmentioning
confidence: 99%
“…Social exchange theory posits that reciprocal relationships constitute a dynamic mechanism in social development. Reciprocity is the exchange of social psychology and social behavior in interpersonal relationships, and the cost of the exchange is not limited to material wealth, but also includes psychological wealth ( Simbula et al, 2023 ). The relationship between an organization and its employees, as governed by the psychological contract, represents a reciprocal exchange.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%